Green transformational leadership, environmental strategy, and green innovation: Mediated moderation of knowledge sharing and green absorptive capacity - Muhammad Siddique Malik; Kamran Ali; Muhammad Amir; Kulsoom Tariq; Muhammad Ramzan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This study explores the impact of green transformational leadership and environmental strategies on promoting green innovation in manufacturing firms in Pakistan. It examines how such leadership and its strategies encourage employees to foster green innovation through effective knowledge-sharing and enhanced green absorptive capacity. The current study was conducted with a sample of 413 respondents collected via survey forms, and the hypotheses were tested using structural equation modeling in AMOS. The findings indicate that green transformational leadership significantly impacts green innovation by supporting subordinates in generating new ideas, products, and policies. Furthermore, environmental strategies strongly influence green innovation, as green vision and strategies are essential for incorporating green innovation. The mediating role of knowledge sharing strengthens the relationship between green transformational leadership and green innovation and between environmental strategy and green innovation. The moderating impact of green absorptive capacity also proved significant. The study concludes that these constructs are vital antecedents of green innovation and provide a solid foundation for sustainable practices. This research contributes to the literature on the natural resource- based view (NRBV) theory and green innovation by highlighting the roles of green transformational leadership, knowledge sharing, and environmental strategy. It offers valuable insights for executives and managers in promoting green innovation within firms and implementing eco-friendly strategies and policies through structured knowledge- sharing.
Keywords: 330; Green transformational leadership; environmental strategy; green innovation; knowledge sharing; green absorptive capacity; manufacturing sector; Pakistan